Analisis Fatwa DSN-MUI terhadap Kontrak Akad Qardh Di Lembaga Keuangan Syariah (Studi Kasus pada BPRS Baiturridha Pusaka) - Muhammad Yunus (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
In Indonesia, there are two financial institutions, namely conventional financial institutions and Islamic financial institutions. Islamic financial institutions in their operations are based on the fatwa that has been issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) as an authoritative institution in issuing fatwas in the field of Islamic economics. Baiturridha Puska, one of the Islamic financial institutions, issued al-qardh financing products. At the level of practice, which is implemented by BPRS Baituttidha Puska that in the contract it is indicated that there is a clause that is different from the provisions of the DSN-MUI fatwa No. 19 of 2001 concerning al-Qardh. The purpose of this study was to determine the concept of the qardh contract in fiqh and the DSN-MUI fatwa and to analyze the qardh financing contract contract at the Baiturridha Pusaka BPRS. This study uses qualitative research, with a normative juridical approach and data collection techniques by means of literature study. The results of the study show that first, the qardh contract is a form of tabarru contract so it is not intended for profit; secondly, the provisions of Article 2 of the Letter of Acknowledgment of Financing contain a clause that is contrary to sharia principles, namely the DSN-MUI fatwa no. 19 of 2001 concerning al-Qardh.